Interactivity as the Model of Reading - Lavrinec, Jekaterina (Problemos, 2002)
In the paper the phenomenon of “interactivity” is investigated on the base of some literal works, determined as “interactive” by their authors and critics as well. The notion of “interactivity” characterizes both the structure of texts and the techniques of reading. As the characteristic of reading (or perception of the text), interactivity is defined through the concept of “author's death”. And as the characteristic of text itself it is defined through the concept of “non-linear writing”. Both aspects are discussed in the article. The interactive works are to be treated as extremums, revealing both the potential of texts as such and the characteristics of the reading itself.
Keywords: interactivity; hypertext; non-linear writing; choreography of reading